First cytogenetic analysis of Ichthyoelephas humeralis (Günther, 1860) by conventional and molecular methods with comments on the karyotypic evolution in Prochilodontidae - Tursellino, Mauro Nirchio; Silva, Duílio Mazzoni Zerbinato de Andrade [UNESP]; Abad, César Quezada; Blacio, Wilmer Arnoldo Moreira; Romero, Omar Rogerio Sánchez; Oliveira, Claudio [UNESP] (Pensoft Publishers, 2016)
We used conventional cytogenetic techniques (Giemsa, C-banding, Ag-NOR), and fluorescent in situ hybridization (FISH) with 5S and 18S rDNA probes to investigate the karyotype and cytogenetic characteristics of Ichthyoelephas humeralis (Günther, 1860) from Ecuador. The specimens studied have a karyotype with 2n=54 biarmed chromosomes (32 M + 22 SM) and C-positive heterochromatin located on the centromeric, pericentromeric, interstitial, and terminal regions of some chromosomes. The nucleolus organizer regions occurred terminally on the long arm of chromosome pair 2. FISH confirmed the presence of only one 18S rDNA cluster with nonsyntenic localization with the 5S rDNA. Cytogenetic data allow us to refute the earlier morphological hypothesis of a sister relationship between Semaprochilodus Fowler, 1941 and Ichthyoelephas Posada Arango, 1909 and support the molecular proposal that Ichthyoelephas is a sister group to the monophyletic clade containing Prochilodus Agassiz, 1829 and Semaprochilodus.
Keywords: Evolution; Fluorescent in situ hybridization; Karyotype; NORs; Prochilodontidae